The light, the dark, and everything else: making sense of young people's digital gaming - Meriläinen, Mikko; Ruotsalainen, Maria (Frontiers in Psychology, 2023)
Whether gaming has a beneficial or detrimental effect on young people’s lives is a defining feature in both the research and the public discussion of youth digital gaming. In this qualitative study, we draw from a thematic analysis of the experiences of 180 game players in Finland, aged 15–25. Utilizing the digital gaming relationship (DGR) theory, we explore how different aspects of gaming actualize in their lives, and how different features of gaming culture participation come together to form their experience. We contend that framing gaming as a balancing act between beneficial and detrimental obscures much of the complexity of young people’s gaming, reinforces a partially false dichotomy, and overlooks young people’s agency. Based on our results, we suggest alternative approaches that help reduce and avoid these problems.